2011
DOI: 10.1007/s10682-011-9501-y
|View full text |Cite
|
Sign up to set email alerts
|

Adult body size = f (initial size + growth rate × age): explaining the proximate cause of Bergman’s cline in a toad along altitudinal gradients

Abstract: Animals that exhibit indeterminate growth obey such a functional relationship: adult body size = f (initial size ? growth rate 9 age). Using this framework, we investigated how and why body sizes of a toad species (Bufo andrewsi) covaried across six altitudes (760-2,100 m) in western China. Towards high altitudes, toads tended to produce large eggs, attain large sizes at metamorphism and have great average age, but grow slowly. This indicated that the former three variables contributed more to the observed alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 47 publications
(43 reference statements)
5
81
2
3
Order By: Relevance
“…Various life history traits and environmental factors may also affect the variation. Liao and Lu (2012) suggested that the starting size (metamorphic size), annual growth rate, and the length of time individuals spent on growing (age) could affect the body size of ectothermic animals such as frogs. A given adult size could be achieved through changing in any one of the above factors or their combination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various life history traits and environmental factors may also affect the variation. Liao and Lu (2012) suggested that the starting size (metamorphic size), annual growth rate, and the length of time individuals spent on growing (age) could affect the body size of ectothermic animals such as frogs. A given adult size could be achieved through changing in any one of the above factors or their combination.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ontogenetic trajectory of females may be different from that of males in anurans (Zhang and Lu 2013). At higher altitudes, when females have longer life-span with higher growth rate after sexual maturity and delay in reproduction (Liao and Lu 2012), these will compensate the low-temperature effects, resulting in no trend of obvious decrease in body size along the altitudinal gradients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among amphibians, few studies on trends in body size variation have been carried out, including nearly 5% of total amphibian species around the world (Ashton 2002;Sch€ auble 2004;Laugen et al 2005; Olalla-T arraga & Rodr ıguez 2007; Adams & Church 2008;Bidau et al 2011;Liao & Lu 2012;Gouveia et al 2013;Boaratti & Da Silva 2015;Liao et al 2015; among others). However, there is a wide range of plausible explanations.…”
Section: Introductionmentioning
confidence: 99%
“…: Watt et al, 2010), в последнее время становится все более популярным поиск закономерностей географической изменчивости у разнообразных групп пойкилотермных животных. В основе таких исследований положено представление о сильном влиянии климатической температуры на формирование размеров особей либо непосредственно в процессе онтогенеза, либо под влиянием отбора, влияющего на размеры или другие характеристики жизненного цикла, жестко связанные с размерами (Angilletta et al, 2004;2004a;Liao, Lu, 2011;Olalla-Tarraga, Rodriguez, 2007). Второе направление в целом также основано на концепции тесной взаимосвязи характеристик жизненных циклов, в том числе и сложных, т. е. состоящих минимум из двух четко выраженных фаз -водной и наземной -таких как у многих видов амфибий.…”
Section: Introductionunclassified